Nível insuficiente de atividade física e exposição ao comportamento sedentário : um estudo comparativo em escolares de Sergipe entre 2011 e 2016 - Ribeiro, Davi Soares Santos (2018)
Introduction: Insufficient physical activity (NIAF) and exposure to sedentary behavior (ECS) are risk behaviors that may adversely affect the health of adolescents. Objectives: To analyze the prevalence of NIAF and ECS and their associations to indicators of socioeconomic status in adolescent schoolchildren in the State of Sergipe in 2011 and 2016. Methods: The study deals with two epidemiological surveys with a cross-sectional design carried out in 2011 and 2016, with a representative sample of students from the State Public Network of Sergipe, comprising 8,143 students (2011 = 3,992, 2016 = 4,151), aged 14 to 19 years. We investigated NIAF and ECS associated with indicators of socioeconomic status. For the statistical analysis, descriptive and chi-square statistics were used. We used the raw and adjusted binary logistic regression. Results: In the first study, the prevalence of NIAF was 83.1% (2011) and 83.5% (2016) and was associated with the age group 14 to 15 years old (OR = 1.38; %: 1.05-1.82), female (2011 = OR: 2.20, 95% CI: 1.83-2.64 / 2016 = OR: 2.03, 95% CI: 1.69- 2.45), adolescents living in rural areas (2011 = OR: 1.23, 95% CI: 1.01-1.50 / 2016 = OR 1.28, 95% CI 1.05-1.57) and that they have illiterate mothers (2011 = OR: 1.97 / 95% CI: 1.27-3.06 / 2016 = OR 1.89; 95% CI: 1.27-2.87). In the second study, the prevalence of SCS was 46.2% (2011) and 44.8% (2016) and was associated with the age group 14 to 15 years old (OR = 1.45, 95% CI: 1.19-1.78 / 2016 = OR: 1.58; 95% CI: 1.28-1.94); (95% CI: 1.27-1.68 / 2016 = OR: 1.22, 95% CI: 1.06-1.40), adolescents living in the urban area ( 95% CI: 1.27-1.72), with monthly family income above two wages (OR = 1.22; 95% CI: 1.05-1.42 / 2016 = OR: 1.48; 2011 = OR: 2.22, 95% CI: 1.83-2.68 / 2016 = OR 1.55, 95% CI: 1.22-1.96) and who have mothers with high school education (2011 = OR : 1.73, 95% CI: 1.32-2.28) and with higher education (2016 = OR: 1.57, 95% CI: 1.16-2.11). Conclusion: It was evidenced the increase in the prevalence of NIAF and a tendency to reduce the ECS, as well as associations to socioeconomic characteristics in adolescents from Sergipe-Brazil. It is suggested interventions in the spaces inside and outside the school to allow the reflection and construction of healthy lifestyles in adolescents.